Network Infrastructure Management: Its Importance to the Organization - Mudzramer A. Hayudini (Natural Sciences Engineering and Technology Journal, 2022)
With the advent of the latest technological advancements that shape today’s world into a more dynamic and interconnected environment, a scrutiny examination of network resources as part of the information and technology (IT) infrastructure is a must-include consideration on the side of every organization. Network infrastructures are designed not just to provide backbone connectivity but must ensure reliability in accordance with the security measures and standards accepted in the field of information and communications technology. This literature review aimed to describe the management of network infrastructure as important in every organization as its communication backbone. Management of the resources deployed in the implementation of the infrastructure should be observed in order to serve its purpose, and that is to provide a high-performing IT environment that promotes secured and uninterruptible communication line to the stakeholders of the organization, leaving each and every one of them satisfied and protected while connected in the network. In conclusion, having a quality IT infrastructure ensures reliability on the part of information transmission and security within the scope of the organization’s internal operations. Regardless of the organization’s nature, administrators or managers must invest in building a standardized infrastructure that is scalable, credible, and cost-effective.